The impact of the Corona pandemic on the increase in public expenditures and its repercussions on development The economic situation in Algeria during the period (2019-2021( - بوشيخي أحمد; سالمي رشيد (مجلة الاجتهاد للدراسات القانونية والاقتصادية, 2022)
The study aims to shed light on the impact of the Corona pandemic on the increase in public spending represented in the expenses of management and equipment, comparing it with the last three years, and highlighting its repercussions on the state’s general budget, as public expenditures are a mirror reflecting the various roles played by the state, as they are considered the most important financial policy tools that it uses to achieve its economic and development goals. The results of the study resulted in a reduction in the size of development projects compared to the financial allocations from oil revenues to confront the Corona virus, which was exacerbated by the decline in oil prices, which negatively affected economic development.